Exploring Local Technology Potential and Community Engagement: The 'The Gade Integrated Farming' Program as a CSR Initiative by PT. Pegadaian for Sustainable Farming: Planning Process - Fitry Enita; Bambang Shergi Laksmono (Cita Konsultindo Research Center, 2024)
The